Endovascular Treatment of Infrarenal Abdominal Aortic Aneurysm with Short and Angulated Neck in High-Risk Patient - Stylianos Koutsias; Georgios Antoniou; Christos Karathanos; Vassileios Saleptsis; Konstantinos Stamoulis; Athanasios D. Giannoukas (Case Reports in Vascular Medicine)
Endovascular treatment of abdominal aortic aneurysms (AAA) is an established alternative to open repair. However lifelong surveillance is still required to monitor endograft function and signal the need for secondary interventions (Hobo and Buth 2006). Aortic morphology, especially related to the proximal neck, often complicates the procedure or increases the risk for late device-related complications (Hobo et al. 2007 and Chisci et al. 2009). The definition of a short and angulated neck is based on length (<15 mm), and angulation (>60°) (Hobo et al. 2007 and Chisci et al. 2009). A challenging neck also offers difficulties during open repairs (OR), necessitating extensive dissection with juxta- or suprarenal aortic cross-clamping. Patients with extensive aneurysmal disease typically have more comorbidities and may not tolerate extensive surgical trauma (Sarac et al. 2002). It is, therefore, unclear whether aneurysms with a challenging proximal neck should be offered EVAR or OR (Cox et al. 2006, Choke et al. 2006, Robbins et al. 2005, Sternbergh III et al. 2002, Dillavou et al. 2003, and Greenberg et al. 2003). In our case the insertion of a thoracic endograft followed by the placement of a bifurcated aortic endograft for the treatment of a very short and severely angulated neck proved to be feasible offering acceptable duration of aneurysm exclusion. This adds up to our armamentarium in the treatment of high-risk patients, and it should be considered in emergency cases when the fenestrated and branched endografts are not available.